PENGARUH KUALITAS LAYANAN, RELATIONSHIP MARKETING DAN KESADARAN MEREK TERHADAP KEPUASAN KONSUMEN (STUDI KONSUMEN PRODUK WARDAH PADA CV.ANUGRAH BHAKTI SENTOSA – BEAUTY KENDARI) - Marleni Suria Ningsih; Nasrul Nasrul; Sinarwaty Sinarwaty (Pascasarjana Universitas Halu Oleo, 2021)
This study aims to determine and analyze: (1) the effect of service quality, relationship marketing, and brand awareness simultaneously have an effect on consumer satisfaction of Wardah Beauty Kendari products, (2) the influence of service quality has a significant effect on consumer satisfaction for Wardah Beauty Kendari products, (3) the influence of relationship marketing has a significant effect on consumer satisfaction for Wardah Beauty Kendari products, (4 ) the influence of brand awareness has a significant effect on consumer satisfaction of Wardah Beauty Kendari products. The population in this study were all consumers of Wardah Beauty Kendari products, the number of active consumers as of June 20 was 146 consumers. The sample size was determined by using the Slovin formula with a sample of 60 respondents, the sampling in this study used the accidential sampling technique. The analytical technique used is multiple linear regression analysis with the calculation process using SPSS 28.The results show that: (1) service quality, relationship marketing, and brand awareness simultaneously have a positive and significant effect on customer satisfaction, (2) service quality has a positive effect. and significant on consumer satisfaction of Wardah Beauty Kendari products, (3) relationship marketing has a positive and significant effect on consumer satisfaction for wardah beauty kendari products, (4) brand awareness has a positive and significant effect on consumer satisfaction for wardah beauty kendari products.Keywords: Service Quality, Relationship Marketing, Brand Awareness, Consumer Satisfaction.